PENGARUH RETURN ON EQUITY, EARNING PER SHARE, DAN DIVIDEN PER SHARE TERHADAP HARGA SAHAM PT BANK TABUNGAN NEGARA TAHUN 2012-2021 - Ega Nurhafifah; Aria Aji Priyanto (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to analyze the effect of Return On Equity, Earning Per Share, and Dividend Per Share on the Share Price of PT Bank Tabungan Negara in 2012-2021. This type of research is descriptive quantitative with data analysis methods used are descriptive statistical analysis, classic assumption test, multiple linear regression analysis, coefficient of determination test (R2), and hypothesis testing (t test and f test) with the help of the Statistical Product and Service program Solution (SPSS) version 26, with a significance level of 0.05 (5%) and the data source used is secondary data. The results of this study indicate that Return On Equity has a negative effect on stock prices. This can be seen from the test results which show that the tcount is -3.167 > ttable 2.44691 with a significance level of 0.019 <0.05, thus HO1 is rejected and Ha1 is accepted. The Earning Per Share variable shows that tcount is 2.954 > ttable 2.44691 with a significance level of 0.025 <0.05, it can be concluded that Earning Per Share has an effect on stock prices thus Ho2 is rejected and Ha2 is accepted. The Dividend Per Share variable shows that tcount is 1.462 < ttable 2.44691 and with a significance level of 0.194 > 0.05, it can be concluded that Dividend Per Share has no effect on stock prices thus HO3 is accepted and Ha3 is rejected. The results of the F test show that Return On Equity, Earning Per Share, and Dividend Per Share simultaneously or together have an influence on stock prices. This can be seen from the value of Fcount 5.237 > Ftable 4.35 a significance value of 0.041 <0.05 it can be concluded that HO4 is rejected and Ha4 is accepted. The coefficient of determination R Square = 0.724 or 72.4%, meaning that the share price as the dependent variable is influenced by Return On Equity, Earning Per Share and Dividend Per Share as independent variables of 72.4% and the remaining 27 .6% is influenced by other variables not explained in this study.